THE USAGE OF BAG BOARD MEDIA TO INCREASE LEARNING RESULT IN SUMMATION FOR INTELLECTUAL DISABILITY STUDENTS - Ika Puji Lestari; Ahmad Samawi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The purpose of this research was to describe of (1) the usage of bag board media, (2) increasing of learning results in summation by using bag board media. This research used classroom action research (CAR). The result showed that (1) using of bag board media make students active in summation learning process (2) using of bag board media can increasing summation learning result for intellectual disibilitystudents in the grade III.